O feed também educa?: a criação artística no Instagram como ação pedagógica não formal - um estudo de caso do Projeto Quadro a Quadro - Barreto, Luiz Guilherme Lupinacci (2024)
Included in the research line New Technologies in Education, of the Postgraduate Program in Education: Curriculum, at PUC-SP, this master's research investigates whether and how occupying the Instagram feed with artistic content can be considered a non-formal pedagogical action, subverting the dispersive and alienating logic of social media. To this end, this study is based on pedagogical theories, such as connectivism, by Siemens (2004); socio-interactionism, by Vygotsky (1984); cultural mediation, by Barbosa (2009); non-formal education, by Gohn (2013); and art as experience, by Dewey (2010). Furthermore, the investigation explores concepts related to the universe of digital sociability, such as the culture of participation and connection, by Jenkins (2009); cyberculture, by Lévy (1999); network society, by Castells (2009); digital social media, by Recuero (2009); algorithmic modulation, by Silveira (2019); and filter bubbles, by Pariser (2012). In order to demonstrate, in practice, a possibility of occupying the Instagram feed with emancipatory content, the study proposes an analysis of the digital project "Quadro a Quadro" carried out by Sesc Pompeia, which uses webcomics as a means to provide space for the enjoyment of art and culture on digital platforms. The research adopts a qualitative and exploratory methodology, using knowledge from case studies (Yin, 2005; Gil, 2009), to critically analyze the pedagogical possibilities of artistic creation and enjoyment on Instagram. Based on the integration of the theoretical basis with the analysis of the results of the case study, the research suggests that, because it is supported by a series of pedagogical intentions, Quadro a Quadro can be considered a non-formal educational action, since it promotes aesthetic and critical education, facilitates networked learning and presents curricular strategies that value cultural formation and active participation of the public. In this way, this work offers a critical reflection on the potential of social media as alternative educational spaces, even though these environments are not originally designed for this purpose